2010
DOI: 10.1590/s0004-282x2010000100020
|View full text |Cite
|
Sign up to set email alerts
|

Carpal tunnel syndrome: treatment with small transverse incision

Abstract: Objective: To evaluate the application of a limited transverse incision technique to treat the carpal tunnel syndrome, with concern to its safety and efficacy in the opening of the flexor retinaculum (FR). Method: A prospective analysis of thirty FR release procedures performed on twenty-eight patients subjected to the proposed incision technique. Safety and total opening of the FR were evaluated through a questionnaire and an endoscopic inspection respectively. results: No major complications were observed. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 29 publications
1
3
0
1
Order By: Relevance
“…In other similar local studies, Mansoor et al, 18 (2017) and Ehsan et al, 19 (2015) reported comparable female predominance with male to female ratio of 1:1.8 and 1:1.7 respectively. Similar female predominance has also been reported by Mardanpour et al, 16 (1:2.7) in India, Yagci et al, 20 (1:2.7) in Turkey and Kalef et al, 21 (1:2.3) in Brazil.…”
Section: Discussionsupporting
confidence: 86%
“…In other similar local studies, Mansoor et al, 18 (2017) and Ehsan et al, 19 (2015) reported comparable female predominance with male to female ratio of 1:1.8 and 1:1.7 respectively. Similar female predominance has also been reported by Mardanpour et al, 16 (1:2.7) in India, Yagci et al, 20 (1:2.7) in Turkey and Kalef et al, 21 (1:2.3) in Brazil.…”
Section: Discussionsupporting
confidence: 86%
“…18 The treatment of CTS falls under two categories: conservative and surgical. Conservative treatmentwith medication, physiotherapy, splinting or local infi ltration can be initially 11…”
Section: Basnet Et Almentioning
confidence: 99%
“…The mini-incision technique tries to combine the lower expense of the open surgeries with the shorter length of stay and reduced scarring of the endoscopic method; however, further studies are needed for its long-term assessment. 15,16 Given the socioeconomic impact (up to US$ 30,000 in the lifetime of each United States worker) of this pathology and the best results obtained with surgical treatment (superiority in functional improvement, in addition to early and longterm regression of the symptoms), 17 the present study tried to define the epidemiological aspects and cost estimates resulting from surgeries performed by the Brazilian Unified Health System (SUS, in the Portuguese acronym) for the treatment of CTS in Brazil between 2008 and 2016.…”
Section: Palavras-chavementioning
confidence: 99%